Indicadores de desempenho para o gerenciamento de manutenções em grandes paradas preventivas - Freitas, Vincentte Weber Batista de (Universidade Federal Rural do Semi-Árido, 2019)
This research aims to list and analyze the main performance indicators of maintenance management at scheduled shutdown events of large production lines. As a strategy, it was adopted a theoretical aspect, based on bibliographic research, and an empirical aspect, with the implementation and analysis of these indicators on a scheduled shutdown at a cement company in the state of Rio Grande do Norte. The results of this research, associated with the best project management practices, made it possible to diagnose the organization's maturity in managing these types of maintenance. Among other aspects, the definition and survey of these indicators are a milestone in the quality management of these events, showing the current situation and the aspects that deserve the concentration of efforts to promote continuous process improvement.
Monografia
Keywords: Indicadores de desempenho; Gestão de projetos; Manutenção Industrial; ENGENHARIAS::ENGENHARIA MECANICA